Miselna proza Vladimirja Bartola - Štuhec, Miran (Slavistična revija, 2006)
Vladimir Bartol's intellectual prose is the nexus of the author's three interests, i. e., psychology, his own personality, and literature. The study analyzes the dialects of this corpus by following the topical emphases, linguistic and stylistic image, and the aspect of literary genre.
Keywords: Bartol, Vladimir; consciousness; criticism; esej; essay; essay writing; Freudian psychoanalysis; Freudova psihoanaliza; intellectual prose; književna esejistika; književnost; kritičnost; literary essay; miselna proza; ne zaključna dela; psihoanaliza; psychoanalysis; zavest